A Matrix-based Algorithm for the Minimax Design of 2-D FIR Filters with Frequency Constraints - Zhang, Xiaoxue; Zhao, Ruijie (Chinese Control Conference, 2018)
An efficient algorithm is proposed for the minimax design of two-dimensional (2-D) linear-phase FIR filters with frequency inequality constraints. The method converts the constrained minimax design problem into a series of unconstrained weighted minimax design problems, where the weighting function is appropriately updated in each iteration. Further, these unconstrained weighted minimax design problems are solved efficiently using a matrix-based iterative reweighted least-squares (IRLS) algorithm. Moreover, the proposed algorithm is guaranteed to converge to the optimal solution provided it exists. Finally, a design example and comparison with existing method are provided to demonstrate the effectiveness and efficiency of the proposed method.